(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
The study pertains to comparative evaluation of CT scan finding and post mortem examination findings in fifty cases of head injury victims. It was observed that although CT scan is a useful tool for the diagnosis of various kinds of lesions of head injury, autopsy was found to be more effective in detecting them.